Analisa Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan Properti dan Real Estate yang Go Public di Bursa Efek Indonesia - Benedicta Amadea (Business Accounting Review, 2013)
This study aimed to analyze the factors that influence the company’s capital structure. This study used several control variables that be identified as factor that influenced the capital structure, such as profitability, firm’s growth, operating leverage, and asset structure. The population used in this study were companies whose businesses are in property and real estate sectors. Hypothesis in this study was tested by using multiple linear regression model. Simultaneous signification test (F test) and partial signification test (t test) with 5% were used to test hypothesis. The result of F test showed that profitability, firm’s growth, operating leverage, and asset structure have significant influence on capital structure simultaneously. The result of t test showed that profitability had negative and significant influence on capital structure. Fims’s growth and operating leverage didn’t have influence on capital structure. And asset structure had postive and significant influence on capital structure.